Qualitative Seismic Evaluation of the Existing UR Masonry Shear Walls – Reinforced Concrete Frames System - Mihai Petru; Sococol Ion (Selected Scientific Papers: Journal of Civil Engineering)
The dual system buildings consisting of Unreinforced Masonry (URM) Shear Walls and Reinforced Concrete (RC) Frames are part of the existing buildings patrimony in Romania. Being a seismic zone, the qualitative evaluation of this type of structural system represents both a specific and a holistic approach. Thus, the in-depth knowledge of the initial situation of the building, including the level of degradation as well as the causes that produced these damages represents the present study. Also, notions such as: the level of degradation importance, the level of damage (destruction), the correction coefficient of the bending stiffness, the level of knowledge, the evaluation methodology are interpreted, in order to establish a score of the degree of seismic configuration of the lateral system and degree of structural damage. This information leads to the establishment of the seismic risk class of the analyzed building and to the establishment of the intervention works necessity.